Syntheses of fluorooxindole and 2-fluoro-2-arylacetic acid derivatives from diethyl 2-fluoromalonate ester - Harsanyi, Antal; Sandford, Graham; Yufit, Dmitri S.; Howard, Judith A.K. (Beilstein Journal of Organic Chemistry, 2014)
Diethyl 2-fluoromalonate ester is utilised as a building block for the synthesis of 2-fluoro-2-arylacetic acid and fluorooxindole derivatives by a strategy involving nucleophilic aromatic substitution reactions with ortho-fluoronitrobenzene substrates followed by decarboxylation, esterification and reductive cyclisation processes.
Keywords: fluorinated building blocks; fluoroarylacetic acid; fluoromalonate; fluorooxindole; organo-fluorine; selective fluorination